Comparison among Three Articles of Instructional Pedagogies : A critical Review on Three Journal Articles Reporting Research about Contemporary Teaching Methods and Current Pedagogical Issues) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This review is aimed at knowing and extending the content of three journal articles reporting research regarding contemporary teaching methods and current pedagogical issues. Reviewer would like to do a review by responding the positive and negative aspects and conduct the critical review to each of the three articles comparatively to know similarities and differences from the contents of each of the three articles. This review is managed into three components namely introduction, summary of articles, and critical review. The results can be conveyed as follows: (1) the article 1 and the article 3 are better than the article 2, from aspects of research title, abstract and methodology, (2) the article 2 and the article 3 are better than the article 1 from angles of introduction, (3) from the angle of the literature review, the article 3 is better than the article 1 and the article 2, and (4) from the aspects of result and discussion, the article 1 is better than the article 2 and the article 3.